Bioaccessible (poly)phenol metabolites from raspberry protect neural cells from oxidative stress and attenuate microglia activation. (15th January 2017) - Garcia, Gonçalo; Nanni, Sara; Figueira, Inês; Ivanov, Ines; McDougall, Gordon J.; Stewart, Derek; Ferreira, Ricardo B.; Pinto, Paula; Silva, Rui F.M.; Brites, Dora; Santos, Cláudia N.
Graphical abstract: Highlights: Raspberry digested metabolites protect neurons and microglia towards H2 O2 and LPS insults. Neuroprotection is independent of intracellular ROS scavenging. Microglial M1 activation by LPS is attenuated by raspberry metabolites. Abstract: Neuroinflammation is an integral part of the neurodegeneration process inherent to several aging dysfunctions. Within the central nervous system, microglia are the effective immune cells, responsible for neuroinflammatory responses. In this study, raspberries were subjected to in vitro digestion simulation to obtain the components that result from the gastrointestinal (GI) conditions, which would be bioaccessible and available for blood uptake. Both the original raspberry extract and the gastrointestinal bioaccessible (GIB) fraction protected neuronal and microglia cells against H2 O2 -induced oxidative stress and lipopolysaccharide (LPS)-induced inflammation, at low concentrations. Furthermore, this neuroprotective capacity was independent of intracellular ROS scavenging mechanisms. We show for the first time that raspberry metabolites present in the GIB fraction significantly inhibited microglial pro-inflammatory activation by LPS, through the inhibition of Iba1 expression, TNF-α release and NO production. Altogether, this study reveals that raspberry polyphenols may present a dietary route to the retardation or amelioration of neurodegenerative-related dysfunctions.